Balance theory and the perception of religious relationships : an application of three quantitative cognitive consistency models in Singapore. - Lim, Wendy Mei Sze. (2008)
This study engages a social psychological approach to explain the formation of attitudes in public opinion, seeking to understand how individuals could be driven by various social forces that impinge on them as they form attitudes towards an issue.